Efficient conversion of crude glycerol from various industrial wastes into single cell oil by yeast Yarrowia lipolytica. (May 2016) - Dobrowolski, Adam; Mituła, Paweł; Rymowicz, Waldemar; Mirończuk, Aleksandra M.
Highlights: Waste glycerol derived from various industries were tested for lipid production. The first study using stearin and soap production wastes for lipid synthesis. Glycerol derived from fat saponification may be used without YE supplementation. A particular fatty acid profile is determined by source of crude glycerol. Abstract: In this study, crude glycerol from various industries was used to produce lipids via wild type Yarrowia lipolytica A101. We tested samples without any prior purification from five different waste products; each contained various concentrations of glycerol (42–87%) as the sole carbon source. The best results for lipid production were obtained for medium containing glycerol from fat saponification. This reached 1.69 g L −1 (25% of total cell dry weight) with a biomass yield of 0.17 g g −1 in the flasks experiment. The batch cultivation in a bioreactor resulted in enhanced lipid production—it achieved 4.72 g L −1 with a biomass yield 0.21 g g −1 . Moreover, the properly selected batch of crude glycerol provides a defined fatty acid composition. In summary, this paper shows that crude glycerol from soap production could be efficiently converted to single cell oil without any prior purification.